La contribution des projets artistiques participatifs à une bonne qualité de vie dans les régions de montagne - Julia Grosinger; Gentiane Desveaux (Revue de Géographie Alpine)
We analysed the role of artistic approaches to evaluate different aspects that contribute to a good quality of life. We showed that certain artistic approaches have levers for action that can be conducive to a good quality of life. The article follows a pragmatic research methodology. It supports artistic creation and analyses the methodological approach of the artists themselves. The authors of this article were embedded in the artistic process. Our case study is a travelling theatre group (http://www.theatredeschemins.org/). They contributed to the co-construction of a walking theatre performance in the Val Venosta in South Tyrol (Alto Adige)/Italy. This allowed us to identify and assess the links between the emotional state of local inhabitants, and identities linked to place and environment based on 17 semi-directive interviews. We hypothesised that artistic approaches reveal factors relevant to a good quality of life that remains invisible by conventional research methods. The scientific support in this process helps to direct their creation towards a transformation and improvement of the quality of life. We discuss three identified aspects that contribute to a good quality of life: (1) Awareness of environmental changes and attachment to a territory; (2) Satisfaction of and a desire for a shared life; (3) Strengthening of (self-)identity.